DOI: 10.15368/theses.2009.41
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Starter Cultures on Lactobacillus Acidophilus Survival and Gene Expression in Yogurt

Abstract: The Effect of Starter Culture on Lactobacillus acidophiluswith the starter cultures. Our future work is to provide a better understanding of strain differences in survival of probiotics in yogurt.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 143 publications
(144 reference statements)
0
2
0
Order By: Relevance
“…At first, pickles were incubated in 35 • C/8 h growing conditions for Lb. acidophilus and Lb.casei (see [21] and [22] for more details) for developing acidity. Then they were incubated at 20 • C/15 d [23] after that they stored in refrigerator at 4 • C. Acidity, viable numbers of Lb.…”
Section: Bacterial Culturesmentioning
confidence: 99%
“…At first, pickles were incubated in 35 • C/8 h growing conditions for Lb. acidophilus and Lb.casei (see [21] and [22] for more details) for developing acidity. Then they were incubated at 20 • C/15 d [23] after that they stored in refrigerator at 4 • C. Acidity, viable numbers of Lb.…”
Section: Bacterial Culturesmentioning
confidence: 99%
“…Other factors influencing the viability of probiotic bacteria in fermented dairy products include hydrogen peroxide produced by starter bacteria, availability of nutrients, osmotic pressure due to presence of sugars, dissolved oxygen, inoculation level, fermentation time and storage temperature (Shah, 2000). Kopeloff et al (1934), Gilliland and Speck (1977) and Ng (2009) found that some strains of L. acidophilus had limited stability in fermented products like traditional acidophilus milk and yogurt because of progressive increase in the acidity of products during storage termed as post acidification since the starter culture bacteria are active at refrigerated temperature.…”
Section: Fermented Dairy Productsmentioning
confidence: 99%